Analisis Kemampuan Berpikir Kritis Ditinjau Dari Keterampilan Proses Sains Melalui Model PjBL Berbantuan Mobile Learning Pada Siswa Kelas V Sekolah Dasar - Putra Setiyawan, Riyan; ST. Budi Waluya; Lusi Rachmiazasi Masduki (Universitas Muhammadiyah Magelang, 2026)
The 2022 PISA results placed Indonesia at a science score of 383, well below the international average of 489, signalling persistent weaknesses in students' critical thinking skills (CTS) and science process skills (SPS). A preliminary survey across Gugus Kartini, Blora Regency, found that 82% of assessment items remained at the C1–C2 cognitive level and only 15.5% of fifth-grade students could communicate observational results scientifically. This study analysed fifth-grade students' critical thinking skills in terms of science process skills through a Project-Based Learning (PjBL) model assisted by QR Code–based mobile learning. A sequential explanatory mixed methods approach was applied, employing a pretest–posttest non-equivalent control group quasi-experimental design with 56 fifth-grade students from SDN 3 Jepangrejo (experimental) and SDN 1 Jepangrejo (control) on the topic of Light and Its Properties. Quantitative data were collected through essay-form CTS tests and SPS observation sheets, while qualitative data were drawn from purposive interviews with six students representing high, medium, and low SPS categories, then analysed using z-tests, independent and paired t-tests, N-gain, simple linear regression, and the Miles–Huberman model. Classical mastery in the experimental class reached 92.86%, with a CTS mean of 83.43 compared with 69.75 in the control class. The experimental class N-gain reached 66.84% (moderately effective), whereas the control class attained only 25.90% (ineffective). Regression analysis confirmed that SPS positively and significantly influenced CTS with a contribution of 77.3%. PjBL assisted by mobile learning is effective in enhancing fifth-grade students' critical thinking skills, and students' CTS profiles consistently correspond to their SPS categories. The findings imply that integrating project-based science instruction with mobile technology constitutes a viable strategy for strengthening 21st-century skills at the primary level.